The women image and the symbolic representation of violence in the discourse of popular proverbs in the Algerian society. - حطاب فتيحة; درويش محمد (International Journal of Social Communication, 2023)
The aim of this study is to shed light on the image of women and explains the mental construction at the level of symbolism in the popular proverb’s speech and analyze its connotations and the of women ’image through the symbols carried in these proverbs. this study was conducted on 40 forty popular proverbs by analyzing the content through the interrogation mechanism of what these proverbs say about women through a descriptive and analytical study, it was done by deciphering the symbols of these proverbs, realizing their contents and the most important images and symbolic representations, so that, to reveal the representation of violence and its forms against women.